Pesan Moral Dalam Film Sore: Istri Dari Masa Depan (Analisis Semiotika Roland Barthes) - Syachzidan Mahadi Dwi Kusuma; Iin Soraya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study discusses the moral message in the film Sore: Istri dari Masa Depan (Sore: A Wife from the Future), which reflects the phenomenon of low individual awareness of the long-term effects of unhealthy lifestyles and daily life choices. Films are positioned as cultural texts that not only serve as entertainment but also as a medium of communication that conveys values and meanings of life. This study uses a qualitative approach with Roland Barthes' semiotic analysis method, which examines visual and verbal signs through three levels of meaning, namely denotation, connotation, and myth. The analysis focuses on several key scenes that depict the conflict between the main characters regarding life changes, sacrifice, and romantic relationships. The results show that this film conveys a moral message about the importance of self-awareness, responsibility for health, and the meaning of love as a form of care and sacrifice for a better future. This study is expected to contribute to communication and film studies in understanding the role of film as a medium for conveying moral messages and encouraging viewers to be more critical in interpreting the messages conveyed through audio-visual works.